Disproportional Ownership Structure and Pay-Performance Relationship in China - CAO, Jerry (Institutional Knowledge at Singapore Management University, 2011)
This paper examines the impact of ownership structure on executive compensation in China's listed firms. We find that the cash flow rights of ultimate controlling shareholders have a positive effect on the pay-performance relationship, while a divergence between control rights and cash flow rights has a significantly negative effect on the pay-performance relationship. We divide our sample based on ultimate controlling shareholders' type into state owned enterprises (SOE), state assets management bureaus (SAMB), and privately controlled firms. We find that in SOE controlled firms cash flow rights have a significant impact on accounting based pay-performance relationship. In privately controlled firms, cash flow rights affect the market based pay-performance relationship. In SAMB controlled firms, CEO pay bears no relationship with either accounting or market based performance. The evidence suggests that CEO pay is inefficient in firms where the state is the controlling shareholder because it is insensitive to market based performance but consistent with the efforts of controlling shareholders to maximize their private benefit.